Using interactive digital narrative in science and health education - Skains, R. Lyle; A. Rudd, Jennifer; Casaliggi, Carmen; J. Hayhurst, Emma; Horry, Ruth; Ross, Helen; Woodward, Kate (Emerald Publishing Limited, 2021)
Both the United Nations and the World Health Organization stress the need to address numerous increasingly urgent 'global challenges', including climate change and ineffectiveness of medication for communicable diseases.Despite climate change resulting from human activity, most humans feel their contribution is minimal; thus any effort made toward reducing individual carbon footprint is futile. Likewise, individual patients feel their health is their own problem; current increases in outbreaks of formerly controllable diseases like measles and tuberculosis show that this is not the case. There is a dire need to instil a stronger sense of personal responsibility, to act as individuals to resolve global issues, and the pilot studies presented in Using Interactive Digital Narrative in Science & Health Education offer an entertainment-as-education approach: interactive digital narrative. The researchers on these teams cross diverse disciplinary boundaries, with backgrounds in chemical engineering, microbiology, romantic studies, film studies, digital design, pedagogy, and psychology. Their approach in Using Interactive Digital Narrative in Science & Health Education to interdisciplinary research is discussed herein, as is the practice-based approach to crafting the interactive narratives for health and science communication and for specific audiences and contexts.
Includes index.
Keywords: Digital storytelling.; Interactive multimedia.; Narration (Rhetoric); Communication in science.; Communication in medicine.; Political Science -- Public Policy / Communication Policy.; Media studies.; elektronické knihy; electronic books